INFLUENCE OF COMBINED HYPOLYPIDEMIC THERAPY ON ACHIEVING TARGETED LDL LEVELS IN PATIENTS WITH IBS AND TYPE 2 DIABETES (Web of Teachers: Inderscience Research, 2026)
Relevance. Patients with coronary heart disease (CHD) and type 2 diabetes mellitus (DM2) belong to the category of very high cardiovascular risk. Despite the widespread use of statins, achieving target levels of low-density lipoprotein (LDL) remains insufficient. Purpose of the study. To evaluate the effectiveness of combined hypolipidemic therapy compared to statin monotherapy in patients with coronary artery disease and type 2 diabetes. Materials and methods. The prospective study included 120 patients with coronary heart disease and type 2 diabetes. The main group (n=60) received combined therapy (statin + ezetimib or PCSK9 inhibitor), while the control group (n=60) received monotherapy with statins. Evaluation was conducted after 12 weeks. Results. In the main group, the decrease in LDL was 54%, and in the control group, it was 32% (p